Understanding medieval Latin with the help of middle Dutch - Bos, Egbert P., author.
1 online resource.
Keywords: How advanced students in the 15th century learned to understand Latin with the help of Middle Dutch becomes clear in Master Simon’s (?) commentary in the form of questions on the famous medieval didactical poem on grammar Doctinale of Alexander de Villa Dei. The master discusses notions such as the six cases of Latin (nominative, genitive, dative, accusative, vocative and ablative), construction, impediments of construction, and participles. The author has a conceptualist approach of language and criticizes interpretations by realists (Modists). He refers to other important medieval grammars, viz. Commentary on Priscian attributed to Peter Helias, Compendium de modis significandi attributed to Thomas of Erfurt, the Metrista, the Regulae Puerorum and the Florista .